Beckman Microzone Plus Membranes (1981)
Made of cellulose acetate, these membranes were designed for use with Microzone Electrophoresis Systems.
Keywords: Electrophoresis; Cellulose acetate; Scientific apparatus and instruments; Beckman Instruments, Inc.